Perancangan Dan Pembuatan Sistem Informasi Pendaftaran Online Berbasis Android Di Rumah Sakit Daerah Balung - Asri Dheajeng Imani; Sustin Farlinda; Andri Permana Wicaksono; Erna Selviyanti (Politeknik Negeri Jember, 2022)
Balung Regional Hospital is a type C hospital belonging to the government of Jember. The Balung Regional Hospital has problems, namely the time of patient attendance and the number of patients not previously known, difficult registration procedures and long registration, excessive waiting time for patients in outpatient services, and the accumulation of patients in outpatient services. The purpose of this study is to design and create an android-based online registration system at the Balung Regional Hospital which is expected to make it easier for patients who register online to get a queue number. Patients can register anywhere, anytime without being limited by space and time. In a system improvement process, this research uses the waterfall model system improvement method. The method begins with analyzing software requirements, designing, coding the system and testing the system. The final result of this research is android-based online registration at the Balung Regional Hospital. The benefit of this research is to improve the quality and quality of service at the Balung Regional Hospital.